Effects of Green Tea (Camellia Sinensis) on Liver Morphology and Body Weight of Mice on High Fat Diet - LIAQAT ALI MINHAS, FARHANA SAJJAD (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study was to evaluate the effects of green tea on liver morphology and weight of mice on high fat diet. Methods: Sixty adult mice, Balb-C strain were selected and divided into three groups. The control group was given standard laboratory diet throughout the study. In experimental group A, the study was carried out in two phases. In the first phase, hepatic steatosis was induced by high fat diet containing 4 percent cholesterol powder and 40 percent butter fat for six weeks. In the second phase, experimental group was given normal diet with 1 percent green tea over a period of next six weeks. The experimental group B was given high fat diet containing 4 percent cholesterol powder and 40 percent butter fat with 1 percent green tea over a period of twelve weeks. Ten mice in each were sacrificed at six weeks & remaining ten were sacrificed at twelve weeks. Results: Showed that high fat diet for six weeks produced significant hepatic steatosis, evident on biochemical analysis. When experimental group A (induction phase) with high fat diet was compared with the (reversal phase) on normal diet and green tea, statistically significant difference (p<0.05) was noted in terms of body weight and morphology / gross parameters in experimental group B, which though reduced never reached the control value and remained somewhat elevated. Conclusion: It is therefore concluded that green tea protects against the development of hepatic steatosis and reduces hepatic injury and body weight in mice.